An empirical analysis of the impact of various dimensions of work-life balance on organizational commitment among service sector employees in India - Mathew, Rincy V.; Panchanatham, N. (Universiti Utara Malaysia, 2010)
The present study examined the relationships of the various facets of work-family balance with organisational commitment (OC) and its various dimensions among employees working in the service sector in India. Data were collected from 408 employees by means of questionnaires. Correlation and linear regression analysis of the collected data demonstrated that while one of the dimensions of work-life balance namely, work interferes with personal life (WIPL), acted as a significant negative predictor of OC, another dimension that is work enhancement/ personal enhancement (WE/PE) showed significant positive impact on OC. The third dimension, personal life interferes with work (PLIW) even though showed a negative correlation; the impact was generally not significant. The article concludes with the managerial implications of the study in service sector industries/institutions.